The relationship between adverse childhood experiences and suicidal behaviors in depressed addicted adults: Mediating role of decision-making styles - Farnaz Shaygan Majd; Somaieh Salehi (Journal of Education and Health Promotion)
Background: Adverse childhood experiences (ACEs) are one of the factors that affect a person’s physical and mental health throughout his life. Also, people’s decision-making style plays a very effective role in people’s performance in facing life events. Therefore, this research was conducted to investigate the mediating role of decision-making styles in the relationship between ACEs and suicidal behaviors in depressed addicted adults. Materials and Methods: In terms of the purpose, the research was fundamental, and the research method was among the descriptive research of the correlation type. The population of this research included depressed, addicted male adults in Rey City during the first three months of 2023. A total of 240 individuals were selected using convenience sampling, based on a correlational design. All the respondents were men, and the majority of people answering the questions were over 45 years old. They were asked to respond to the ACEs questionnaire, the decision-making styles questionnaire, the Patient Health Questionnaire-9, and the revised suicidal behavior questionnaire. This research uses descriptive statistics methods including frequency, mean and standard deviation, and inferential methods including model structural equations (path analysis). Results: The findings of this research showed that the direct paths of ACEs on immediate decision-making style (β = 0.18, P = 0.039) and suicidal behaviors (β = 0.45, P = 0.001) are positively significant. Also, the direct path of immediate decision-making style on suicidal behaviors (β = 0.29, P = 0.001) was also positively significant. The results of the bootstrap test showed that the indirect path of ACEs on suicidal behaviors due to immediate decision-making style is also positive and significant (β = 0.05, P = 0.015). Conclusion: Based on mental health policies, it is necessary to organize comprehensive suicide prevention, treatment, and support programs for mental health experts, patients, and families at different levels related to decision-making skills and ACEs.